Prevention of non-contact anterior cruciate ligament injuries in sports. Part II: systematic review of the effectiveness of prevention programmes in male athletes - Alentorn-Geli, E.; Mendiguchia, J.; Samuelsson, K.; Musahl, V.; Karlsson, J.; Cugat, R.; Myer, G. D. (Knee surgery, Sports Traumatology. Arthroscopy, 2018)
Purpose: To synthesize the results of systematic literature review focused on the effectiveness of anterior cruciate ligament (ACL) injury prevention programmes in male athletes. Methods: All abstracts and articles of potential interest identified through the systematic literature search were reviewed in detail to determine on inclusion status. Information regarding prevention programmes to reduce ACL injuries or to modify risk factors for ACL injuries in male athletes was systematically extracted and included intervention and study design, characteristics of participants, sport and level of competition, characteristics of prevention programmes, results, and conclusions. All studies were evaluated for methodological quality to assess the risk of bias. Results: The principal findings of this systematic review are as follows: (1) most of the studies applied prevention programmes that utilized risk factors as outcomes of interest as opposed to ACL injury incidence (5 and 2 studies, respectively); (2) the effectiveness of prevention programmes to reduce ACL injuries in male athletes is equivocal (1 in favour, 1 against) and only refers to soccer players; (3) the effectiveness of prevention programmes to modify risk factors for ACL injuries in male athletes is controversial (2 in favour, 3 against) and outcome data are limited to cutting manoeuvres. Conclusion: Data regarding the effectiveness of prevention programmes to reduce ACL injuries or to modify risk factors for ACL injuries in male athletes are scarce and not conclusive. Future research to better determine the most effective approaches to optimize the effectiveness of prevention programmes targeted to reduce ACL injuries in male athletes is warranted.